Neurobiology of Aggressive Behavior—Role of Autoantibodies Reactive With Stress-Related Peptide Hormones - Vaeroy, Henning; Schneider, Frida; Fetissov, Sergueï O. (Frontiers in Psychiatry, 2019)
This review contributes a mechanistic view on the neurobiology of aggression by summarizing some human and experimental data implicating autoantibodies (autoAbs) reactive with stress-related peptides in aggressive behavior. Peptide hormones including vasopressin, oxytocin and adrenocorticotropin (ACTH) are well known modulators of the stress axis, motivated behavior and emotion relevant to the mechanisms of aggressive behavior. Recently, immunoglobulins (Ig) or autoAbs reactive with these peptide hormones have been identified in humans and rodents showing associations of their plasma levels with aggressive or antisocial behavior, anxiety and depression. The functional role of ACTH autoAbs in modulating the peptidergic signaling and motivated behavior including aggression has been demonstrated in experimental and in vitro models. Since the production of autoAbs is dependent on specific antigens, including those produced by gut bacteria, studies linking the microbial origin of peptide hormone-reactive IgG with peptidergic signaling and stress response may help to better understand the neurobiology of aggressive behavior.